Propolis and vegetable wax in the conservation of Hass avocado Própolis e cera vegetal na conservação de abacate Hass - Ricardo de Oliveira Orsi (Semina: Ciências Agrárias, 2012)
The aim of this work was to evaluate the quality of Hass avocado submitted to application of propolis and vegetable wax. The selected fruits were submitted to the treatments (1) without wax and without propolis, (2) with vegetable wax, (3) propolis alcoholic extract 100%, (4) wax and etanol 70%, (5) propolis alcoholic extract 2% and wax, (6) propolis alcoholic extract 4% and wax, (7) propolis alcoholic extract 6% and wax, (8) propolis alcoholic extract 8% and wax, and (9) propolis alcoholic extract 10% and wax. The fruits were maintained under refrigeration (10 ± 1 ºC and 90 ± 5% relative humidity), being appraised every three days for 15 days and more 3 days of commercialization simulation at room temperature (23± 1 ºC and 18% relative humidity).The evaluation parameters were the weight loss, respiratory activity, pH, firmness, tritable acidity (AT), soluble solids (SS), and ratio. The results of weigth loss, respiratory activity and firmness were the most significant to show the difference among the treatments. ‘Hass’ avocado fruits submitted the application of propolis associated the vegetable wax present smaller weight loss, CO2 production and firmness in relation to the control fruits. The fruits of the treatment with propolis alcoholic extract 2% and wax presented the most promising results. Objetivou-se neste trabalho avaliar a aplicação de própolis e cera vegetal na qualidade pós-colheita do abacate ‘Hass’. Os frutos selecionados foram submetidos aos tratamentos (1) sem cera e sem própolis, (2) com cera vegetal, (3) extrato alcoólico de própolis 100%, (4) cera e etanol 70%, (5) extrato alcoólico de própolis 2% e cera, (6) extrato alcoólico de própolis 4% e cera, (7) extrato alcoólico de própolis 6% e cera, (8) extrato alcoólico de própolis 8% e cera e (9) extrato alcoólico de própolis 10% e cera. Os frutos foram mantidos sob refrigeração (10 ± 1 ºC e 90 ± 5% umidade relativa), sendo avaliados a cada três dias durante 15 dias e mais 3 dias de simulação de comercialização em temperatura ambiente (23± 1 ºC e 18% umidade relativa). Os parâmetros de avaliação foram a perda de massa, atividade respiratória, pH, firmeza, acidez titulável (AT), sólidos solúveis (SS) e ratio. Os resultados de perda de massa, atividade respiratória e firmeza foram os mais significativos para mostrando diferença entre os tratamentos. Frutos de abacate ‘Hass’ submetidos à aplicação de própolis associado a cera vegetal apresentam menor perda massa, produção de CO2 e firmeza em relação aos frutos controle. Os frutos do tratamento com extrato alcoólico de própolis 2% e cera apresentaram os resultados mais promissores.